Effects of imidacloprid on viability and increase of reactive oxygen and nitrogen species in HepG2 cell line - Guimarães, Anilda Rufino de Jesus Santos [UNESP]; Bizerra, Paulo Francisco Veiga [UNESP]; Miranda, Camila Araújo [UNESP]; Mingatto, Fábio Erminio [UNESP] (Taylor & Francis, 2022)
Imidacloprid (IMD) is a neonicotinoid insecticide used in large quantities worldwide in both veterinary and agronomic applications. Several studies have shown adverse effects of IMD on non-target organisms, with the liver being identified as the main affected organ. This study aimed to evaluate the effects of IMD on human hepatoblastoma (HepG2) cells. HepG2 were exposed to IMD (0.25–2.0 mM) for 24 and 48 h. IMD treatment resulted in cytotoxicity in the HepG2, inhibiting cell proliferation in a dose- and time-dependent manner, starting at concentrations of 0.5 mM (24 h) and 0.25 mM (48 h), and reducing cell viability from 0.5 mM onwards (24 and 48 h). IMD significantly decreased the mitochondrial membrane potential at both time points investigated (2.0 mM), and also induced damage to the cell membrane, demonstrated by significant dose and time-dependent increases in lactate dehydrogenase (LDH) release from concentrations of 1.0 mM (24 h) and 0.5 mM (48 h) upwards. IMD treatment also increased the production of reactive oxygen and nitrogen species (ROS/RNS) at rates above 50% following 0.5 mM (24 h) or 0.25 mM (48 h) concentrations, and caused a significant decrease in reduced/oxidized glutathione ratio (GSH/GSSG), indicating oxidative stress. Furthermore, the antioxidant dithiothreitol, which reacts with ROS/RNS and acts as a thiol reducing agent, inhibited the cytotoxic effect of IMD. In addition, the metabolite IMD-olefin was more toxic than IMD. Our results indicate that IMD induces cytotoxicity in HepG2 cells and that this effect may be associated with an increase in the generation of ROS/RNS.
Keywords: cell death; Cytotoxicity; insecticide; liver; oxidative stress